Potamogeton ×clandestinus (P. crispus × P. natans, Potamogetonaceae), a new natural pondweed hybrid discovered in Europe - Bobrov, Alexander A.; Zalewska-Gałosz, Joanna; Chemeris, Elena V. (Phytotaxa, 2013)
In this paper Potamogeton ×clandestinus (Potamogetonaceae), a hybrid between P. crispus and P. natans, is described and illustrated. Hybrid populations were discovered in the rivers Koloshma, Nozhema and Suda in the northern part of European Russia (Vologda reg., Babaevo distr.). Confirmation of the hybrid origin is based on morphological and anatomical data and independently was tested by a direct sequencing of the nuclear ribosomal ITS region and rpl32-trnL intergenic spacer of chloroplast DNA. The additive ITS sequence pattern confirmed that P. ×clandestinus is a hybrid between P. crispus and P. natans. The rpl32-trnL intergenic spacer data revealed that P. crispus was the maternal parent of the hybrid. A detailed morphological and ecological description of P. ×clandestinus is provided and the taxonomic differences between the new hybrid and similar taxa are outlined.